2019
DOI: 10.1128/aem.00761-19
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Expression of Small Secreted Protein 1 (Ssp1) Alters Patterns of Development and Metabolism in the White-Rot Fungus Pleurotus ostreatus

Abstract: The function of small secreted proteins (SSPs) in saprotrophic fungi is, for the most part, unknown. The white-rot mushroom Pleurotus ostreatus produces considerable amounts of SSPs at the onset of secondary metabolism, during colony development, and in response to chemical compounds such as 5-hydroxymethylfurfural and aryl alcohols. Genetic manipulation of Ssp1, by knockdown (KDssp1) or overexpression (OEssp1), indicated that they are, in fact, involved in the regulation of the ligninolytic system. To elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Probably the most interesting feature of SSCPs is their abundant secretion in liquid medium (up to 20%–30% of the total secretome) (Pellegrin et al ., 2015 ; Feldman et al ., 2020 ; Gao et al ., 2020 ) and the unusually high polymorphism of their primary structures (Gaderer et al ., 2014 ; KrizsĂĄn et al ., 2019 ). Some SSCPs have a long evolutionary history of gene duplications (GDs) and lateral gene transfers (LGTs), making them frequent members of the orphomes (the genome fraction comprising orthologue‐less genes) of individual fungal taxa (Przylucka et al ., 2017a ; Feldman et al ., 2019 ; Gao et al ., 2020 ). Paradoxically, despite the abundance of SSCPs in fungal secretomes, functions have been proposed for only a few, while the role of the majority of them remains unknown (Aimanianda and Latge, 2010 ; Feldman et al ., 2017 ; Wang et al ., 2019 ; Gao et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probably the most interesting feature of SSCPs is their abundant secretion in liquid medium (up to 20%–30% of the total secretome) (Pellegrin et al ., 2015 ; Feldman et al ., 2020 ; Gao et al ., 2020 ) and the unusually high polymorphism of their primary structures (Gaderer et al ., 2014 ; KrizsĂĄn et al ., 2019 ). Some SSCPs have a long evolutionary history of gene duplications (GDs) and lateral gene transfers (LGTs), making them frequent members of the orphomes (the genome fraction comprising orthologue‐less genes) of individual fungal taxa (Przylucka et al ., 2017a ; Feldman et al ., 2019 ; Gao et al ., 2020 ). Paradoxically, despite the abundance of SSCPs in fungal secretomes, functions have been proposed for only a few, while the role of the majority of them remains unknown (Aimanianda and Latge, 2010 ; Feldman et al ., 2017 ; Wang et al ., 2019 ; Gao et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the KDssp1 had a longer tropohase, the strain did not generate pigmentation and no lysis of the colony occurred. Taken together, Ssp1 was shown to be involved in the transition from tropohase to idiophase, aging, and metabolism (Feldman et al, 2019), along with regulating ligninolytic enzyme production (Feldman et al, 2017). Overexpression of Ssp1 also negatively affected fruiting body initiation (Feldman et al, 2019), which is in line with KrizsĂĄn et al (2019), who suggested that SSPs function as fruiting body effectors.…”
Section: Ssp1 In P Ostreatus -A Case Studymentioning
confidence: 82%
“…In fungi, QS has been described to regulate processes such as sporulation, secondary metabolite production, morphological transition and enzyme secretion (Barriuso et al, 2018). The effects of Ssp1 in P. ostreatus highly resemble the mentioned characteristics of QS (Feldman et al, 2017(Feldman et al, , 2019. The majority of the known fungal QS molecules are chemical compounds, such as farnesol and alcohol tyrosol, like in Candida albicans (Albuquerque and Casadevall, 2012;Franceschetti et al, 2017;Barriuso et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse strategies utilized by fungal individuals might confer flexibility towards local changes in the environment to increase their fitness, which may be partly derived from elaborately regulated gene expression profiles in response to diverse conditions [26]. Fungi have hundreds or even over a thousand predicted secreted proteins, among which the proportion of SSPs in most fungi is 25% to 60% across all lifestyles [27][28][29]. In this study, H. parviporum was predicted to have 21.4% HpSSPs in its secretome (163/759).…”
Section: Discussionmentioning
confidence: 99%